An iridium N-heterocyclic carbene complex [IrCl(CO)2(NHC)] as a carbon monoxide-releasing molecule (CORM) - Simpson, Peter; Radacki, K.; Braunschweig, H.; Schatzschneider, U. (2015)
© 2014 Elsevier B.V. All rights reserved. Abstract Four NHC complexes of rhodium and iridium of the general structure [RhI(COD)(NHC)], [IrCl(COD)(NHC)], [IrCl(CO)2(NHC)], and [Ir(N3)(COD)(NHC)] (NHC = N-heterocyclic carbene) were synthesised and characterised, including X-ray structure determination for all three iridium compounds. Release of carbon monoxide from [IrCl(CO)2(NHC)] occurred via a rapid bolus of CO on a very short timescale, independent of whether the experiment was performed in the dark or with UV-light illumination, thus establishing the compound as a novel ligand-exchange triggered CO-releasing molecule (CORM). The azide complex represents the first iridium-NHC complex containing an azide ligand.